2014
DOI: 10.1371/journal.pgen.1004334
|View full text |Cite
|
Sign up to set email alerts
|

The Proper Splicing of RNAi Factors Is Critical for Pericentric Heterochromatin Assembly in Fission Yeast

Abstract: Heterochromatin preferentially assembles at repetitive DNA elements, playing roles in transcriptional silencing, recombination suppression, and chromosome segregation. The RNAi machinery is required for heterochromatin assembly in a diverse range of organisms. In fission yeast, RNA splicing factors are also required for pericentric heterochromatin assembly, and a prevailing model is that splicing factors provide a platform for siRNA generation independently of their splicing activity. Here, by screening the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…Interestingly, splicing factors have also been associated with TGS, such as the SR45 protein that is required to establish RdDM and 24-nucleotide siRNA processing at FLOWERING WAGENINGEN (FWA) transgenes 89 . However, Pol IV-dependent transcripts involved in RdDM activity appear to be unspliced 90 , supporting the idea that SR45 participates in RdDM indirectly, perhaps by regulating the splicing of RdDM components, as has been proposed in S. pombe 9194 .…”
Section: Secondary Sirna Biogenesis and Controlsupporting
confidence: 67%
“…Interestingly, splicing factors have also been associated with TGS, such as the SR45 protein that is required to establish RdDM and 24-nucleotide siRNA processing at FLOWERING WAGENINGEN (FWA) transgenes 89 . However, Pol IV-dependent transcripts involved in RdDM activity appear to be unspliced 90 , supporting the idea that SR45 participates in RdDM indirectly, perhaps by regulating the splicing of RdDM components, as has been proposed in S. pombe 9194 .…”
Section: Secondary Sirna Biogenesis and Controlsupporting
confidence: 67%
“…However, earlier biochemical purifications demonstrated that the RDRC subunit Cid12 forms RDRC-independent complexes with splicing factors 27 . Moreover, the RNAi defect found in several splicing mutants can be partially rescued by the introduction of cDNAs that encode RNAi components 45 , suggesting that the effects of splicing mutations on heterochromatic silencing are at least partially due to improper splicing of pre-mRNAs that encode RNAi proteins.…”
Section: Rnai-mediated Heterochromatin Assemblymentioning
confidence: 99%
“…Due to the effect of C-terminal tags on the functionality of Tpz1 (Kallgren et al 2014), the Tpz1-I501R and Tpz1-I200R used in this study were constructed without any tags unless otherwise noted. All strains containing tpz1Δ and pot1Δ were first constructed in diploid cells, followed by tetrad dissection to obtain desired haploid colonies.…”
Section: Fission Yeast Strains and Genetic Analysesmentioning
confidence: 99%